Testate amoebae composition (Amoebozoa: Rhizopoda) associated to the rizosphere of Eichhornia crassipes (Martius) Solomons (Pontederiaceae) in Cachoeira River, Bahia, Brazil: New records for Northeast - Silva, Márcio Borba da; Ribeiro, Sylvia Maria M. S.; Velho, Luiz Felipe Machado (SITIENTIBUS série Ciências Biológicas, 2009)
Studies on microorganisms associated or adhered to aquatic macrophytes are scarce. Due to the important role that testate amoebae (Amoebozoa: Rhizopoda) have in the metabolism of inland waters and the scarcity of information about diversity of this group, the objective of this study was to characterize the composition of testate amoebae associated with Eichhornia crassipes stands in this river, in two hydrologic periods. This work registered 115 taxa of testate amoebae associated to the rizosphere of E. crassipes, belonging to 10 families, 14 genera, 96 species and 19 varieties, distributed in Difflugiidae (42 taxa), Arcellidae (21 taxa), Centropyxidae (14), Euglyphidae, Lesquereusiidae (11 each), Cryptodifflugiidae (7), Trigonopyxidae, Trinematiidae (3 each), Hyalospheniidae (2), and Cyphoderiidae (1). The high richness of testate amoebae are registered in the flood periods river. However, high similarity was observed within the assemblage composition in two hydrological periods. This work includes 84 new registers of tecamebas for the Northeast of Brazil, thus totalizing 137 taxa for this region, and for Bahia State it was recorded 112 new occurrences, what demonstrates the necessity to increase the efforts of collection in the state.